Хора ольвійського поліса (до історії наукової розробки проблеми) - Буйських, С.Б. (Археологія, 2007)
Розглянуто проблему наукової ідентифікації у вітчизняній історіографії середини ХХ ст. території Нижнього Побужжя, передусім пов’язаної з ім’ям Л.М. Славіна, його учнів та колег, як античної землеробської хори Ольвійського поліса. До настоящего времени в научной литературе период исследования сельской округи Ольвии начала 1940-х — конца 1960-х — начала 1970-х гг. обычно оценивался с сугубо археологической точки зрения. В статье предлагается
первый ретроспективный анализ отечественной историографии середины ХХ ст., в первую очередь, связанной
с именем Л.М. Славина, его коллег (Ф.М. Штительман, Я.В. Доманского, В.Д. Блаватского) и учеников (В.В.
Лапина, В.Л. Зуца и др.), в результате научных разработок которых территория Нижнего Побужья была впервые
идентифицирована как хора античного (Ольвийского) полиса, а также определены ее примерные размеры и намечены основные этапы развития. To this day in scientific literature the period from the early 40s till the late 60s of the 20th c. of the research of Olbian
rural neighbourhood has been usually assessed solely from the archaeological point of view. This article presents the
first retrospective analysis of the home historiography of the mid 20th c. related chiefly with the name of L.M. Slavin
and his colleagues F.M. Shtitelman, Ya.V. Domanskyj, V.D. Blavatskyj, as well as disciples V.V. Lapin, V.L. Zuts,
and others. As a result of their scientific elaborations the territory of Lower Buh River region for the first time was
identified as the chora of ancient (Olbian) polis the approximate size of which was determined and the main stages of
the development traced.